Leksikon dalam Upacara Inti Fangowai Fame’e Afo di Kota Medan: Sebuah Kajian Antropolinguistik - Gulo, Restu Niati; Suyanto, Suyanto (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2023)
In the current era of the millennial generation, many cultures have entered which makes local culture have to adapt and acculturate in order to maintain its existence. Therefore, in order to study and overcome local culture, the authors conducted research related to culture, especially culture at the wedding ceremony of the Nias Fangowai and Fame'e Afo people in Medan City. The purpose of this study is to find and describe the shape of the lexicon, cultural meaning and local wisdom in the fangowai and fame'e afo ceremonies. The method used in this study is a qualitative descriptive method with anthropolinguistic theory. Provision of data using interview methods and literature study. The presentation of the results of data analysis is carried out informally. The results of this study found 54 lexicons which were classified into two groups of word class categories, namely the category of nouns or nouns and the category of verbs or verbs. The noun category obtained 31 lexicons accompanied by cultural meanings and local wisdom values and the verb category obtained 23 lexicons accompanied by cultural meanings and local wisdom values.